Effectiveness of Herbal Compress Ball on Reducing Back Pain in Postpartum Women - Deni Maryani; Dara Himalaya; Sri Nengsi Destriani (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Postpartum women tend to experience low back pain disorders due to the labor process and muscle tension, especially when breastfeeding their babies. Efforts to overcome back pain in postpartum women include the use of compresses. One of the non-pharmacological interventions employed is using herbal compress balls, which have aromatherapeutic properties and facilitate heat conduction. This intervention aims to enhance local blood circulation in pain-affected regions. The study was to determine the effectiveness of herbal compress balls in reducing back pain in postpartum women. The measuring tool for assessing the pain scale is the NRS. The method of research is an experimental “one-group pre-post test design”. 96 respondents were selected via non-probability sampling in the form of an accidental sampling technique. Data analysis using the “Wilcoxon signed rank test”. The study showed a reduction in the back pain scale of postpartum women after the use of the herbal compress ball